2010
DOI: 10.1007/s00380-010-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

The S447X variant of lipoprotein lipase gene is inversely associated with severity of coronary artery disease

Abstract: Hyperlipidemia is a major risk factor for coronary artery disease (CAD). Lipoprotein lipase (LPL) is an important enzyme in lipoprotein metabolism. S447X polymorphism of the LPL gene has been implicated in the pathogenesis of CAD. Carriers of X447 allele were reported to have lower triglyceride and higher high-density lipoprotein cholesterol levels as well as a reduced risk of CAD. We hypothesized that S447X gene polymorphism might have a protective effect for CAD. A total of 178 subjects (mean age 42.97 ± 6.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…In a previous study, LPL S447X mutation was shown to have a naturally occurring gain-function [18]. This LPL mutation S447X is the only mutation that has a protective effect against the development of HTG and coronary heart disease by decreasing plasma TG levels in the clinic and increasing HDL production [19]. Thus, gene therapy using the S447X variant has shown therapeutic promise in the study of LPL deficiency [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, LPL S447X mutation was shown to have a naturally occurring gain-function [18]. This LPL mutation S447X is the only mutation that has a protective effect against the development of HTG and coronary heart disease by decreasing plasma TG levels in the clinic and increasing HDL production [19]. Thus, gene therapy using the S447X variant has shown therapeutic promise in the study of LPL deficiency [20].…”
Section: Discussionmentioning
confidence: 99%
“…36 Agirbasli M et al reported that the S447X variant of the LPL gene is inversely associated with severity of CHD and lower TG and HDL-C levels. 37 Also in a recent study, the LPL gene polymorphism was shown to be associated with the consumption of alcohol and unsaturated fat and to modulate serum HDL-C levels. Specifically, the X allele was positively associated with HDL-C concentrations (p<0.001).…”
Section: Discussionmentioning
confidence: 94%
“…Several genetic LPL mutations and metabolic disturbances that alter the lipid and lipoprotein metabolism have been reported as CAD risk factors. (20).…”
Section: Introductionmentioning
confidence: 99%